2017
DOI: 10.7461/jcen.2017.19.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approaches for Symptomatic Cerebral Cavernous Malformations of the Thalamus and Brainstem

Abstract: ObjectiveSurgical resection of thalamic and brainstem cerebral cavernous malformations (CCMs) is associated with significant operative morbidity, but it may be outweighed, in some cases, by the neurological damage from recurrent hemorrhage in these eloquent areas. The goals of this retrospective cohort study are to describe the technical nuances of surgical approaches and determine the postoperative outcomes for CCMs of the thalamus and brainstem.Materials and MethodsWe reviewed an institutional database of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Researchers identified prior hemorrhage as a major risk factor for subsequent hemorrhage 7 , 9 , 41 43 . Localized in deep regions of the brain, brainstem CCM and thalamic CCM took up approximately one-third 44 and it was found that CCM lesions at the brainstem increased hemorrhage rate 12 , 45 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers identified prior hemorrhage as a major risk factor for subsequent hemorrhage 7 , 9 , 41 43 . Localized in deep regions of the brain, brainstem CCM and thalamic CCM took up approximately one-third 44 and it was found that CCM lesions at the brainstem increased hemorrhage rate 12 , 45 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we must always consider vascular malformations, including CMs, in the differential diagnosis of patients with ICH regardless of the volume of the hematoma. When intraoperative findings suggest the presence of CM, complete surgical removal should be the goal of treatment to prevent postoperative hemorrhage because residual CMs have been reported to increase the risk of re-hemorrhage [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…12,13) This approach has two major advantages: first, craniotomy is simple and quick, and the midline approach avoids damage to the brain surface. 12,14) Second, the final surgical view is good, and the entire floor of the third ventricle can be observed, even if the lesion extends into the thalamus. 12,14) Conversely, two major points were observed in this approach: first, disconnection syndrome may occur with callosotomy, and callosotomy should be performed at !…”
Section: Choice Of Approach For Midbrain Cavernous Malformationsmentioning
confidence: 99%
“…12,14) Second, the final surgical view is good, and the entire floor of the third ventricle can be observed, even if the lesion extends into the thalamus. 12,14) Conversely, two major points were observed in this approach: first, disconnection syndrome may occur with callosotomy, and callosotomy should be performed at ! 2 cm to prevent this disorder.…”
Section: Choice Of Approach For Midbrain Cavernous Malformationsmentioning
confidence: 99%